Synthesis and physico-chemical studies of a novel bis [3,5-diamino-4H-1,2,4-triazol-1-ium] dichloride monohydrate - Mrad, Mohamed Lahbib; Ben Nasr, Mahjouba; Dhaouadi, Hassen; Ben Nasr, Cherif (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The title new compound, (C2H6N5+)2, 2Cl−.H2O, contains two 3,5-diamino-4H-1,2,4-triazol-1-ium cations, two chloride anions and one water molecule. The crystal structure is stabilized by O - H···Cl, N - H···Cl, N - H···O and N - H···N hydrogen bonds, one of them being a three-center interaction. Strong π - π stacking interactions between neighboring triazolium rings are present, with a centroid - centroid distance of 3.338 (7) Å. The exocyclic N atoms are sp2 hybridized, as evidenced by bond lengths and angles, in agreement with an enamine-imine tautomerism. A dielectric spectroscopic study of the title compound was performed. The 13C CP-MAS NMR spectrum is in agreement with crystallographic data. The infrared spectrum has been recorded at ambient temperature and interpreted on the basis of literature data. The temperature dependence of the imaginary part of the permittivity constant was analyzed with the Cole - Cole formalism in the temperature range 325 - 375 K.